Implementation of Transformational Leadership in Improving The Performance of Teachers and Employees in Ma Hasyim Asy'ari Pare Kediri - Moh Khoirul Anwar (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Abstract: This research was intended to explore and transform science into an integral and operational system of Islamic education. The approach in this study was quantitative while qualitative analysis was still concidered. There were two variables in this study, guidance and counseling as independent variables, and student learning achievement as the dependent variable. Guidance and counselling variables were estimated to affect student achievement. The source of this research data was obtained by observation, interview, questionnaire and documentation methods. The results of this study proved that guidance and counseling services affected the process of improving student learning achievement. This was based on questionnaire score data that had been calculated with the product moment formula that produced a correlation index value (rxy) of 0.681. These results proved to be greater than the significance values at 1% of 0.463 and 5% of 0.361. Thus, the quality, effective, and ideal education was one that integratef three main areas of activity in synergy i.e. the field of administration and leadership, instructional fields or curricular, and the field of guidance and counseling. Education that only carried out administrative and instructional fields by ignoring the field of guidance and counseling would only produce smart and skilled students in academic aspects but with lack of ability or maturity in the aspect of personality. Keywords: Transformational leadership, teacher performance, MA Hasyim Asy’ari